Basic science process skills of biology laboratory practice: improving through discovery learning - B Bahtiar; Nurhayati Dukomalamo (Biosfer: Jurnal Pendidikan Biologi, 2019)
Biology laboratory practice that applies the discovery learning model is expected to complement all necessary science process needed by the students during the learning activity. The research was an experiment of learning to find the differences in learning outcome in the form of students’ science process skills between discovery learning and the conventional model of biology laboratory practice. The research is conducted at the Public Junior High School 4, Ternate City for the 8th-grade students from October to December 2018. The research instrument used basic science process skills is observation sheet. The indicator of basic science process skills consists of observing, classifying, measuring, communicating, inferring, and predicting. The result of research data analysis shows that t count value was 4.261 with the significance of 0.000. The discovery learning model of biology laboratory practice is better in improving students’ basic science process skills than the learning model of conventional laboratory practice. According to the result, it was concluded that there were differences in students' basic science process skills between the discovery learning model and the conventional model of Biology laboratory practice. Discovery learning model of biology laboratory practice was better in improving the student's basic science skill than the conventional model.